KAIDAH PELESAPAN DALAM KONSTRUKSI KALIMAT MAJEMUK BAHASA INDONESIA - Teguh Setiawan (LITERA, 2005)
This research study aims to describe the rules of ellipsis in compound andcomplex sentences. The sources of the data were two newspapers, Kompas andKedaulatan Rakyat, the edition of March 2002. The data were collected by usingobservation and recording techniques. They were then analyzed by the substitutionmethod. On the basis of this method, the omission and substitution techniques wereemployed.Based on the analysis of the findings, the subject, predicate and object ellipsiscan be found in compound sentences and the subject ellipsis in complex sentences.The rules of ellipsis in compound sentences are that (1) the omission can be doneif the omitted element is the same; (2) the omission of the subject and predicate isalways made in the clause after the coordinative conjunction and the omission of theobject is made in the clause before the coordinative conjunction; (3) the referentialcharacteristic of the omitted element is always anaphoric. The rules of ellipsis incomplex sentences are that (1) the omitted element must be the same; (2) the omittedelement is in the clause preceded by a subordinative conjunction or the dependentclause; (3) the referential characteristic of the omitted element is cataphoric oranaphoric.